Answer: The answer is Yes.
Explanation:
First since both equations are equal to Y you need to set them equal to each other to find the value of x. After you find the value of x, you plug that value into the original equation to find y.
1. 5x-7 = 2x+2 (set equal)
2. 5x-2x = 7+2 (combine like terms) ( I subtracted two from both sides and added 7 to both sides)
3. 3x = 9 ( Divide by 3 to get variable by itself)
4. X = 3
Next, plug the value of x into the original equations. (Use a calculator to speed the process up)
A. Y= 5(3) - 7
Y = 8
B. Y= 2(3) + 2
Y = 8